First-principles calculation of interactions between vacancies in transition-metal aluminides - J.M. Koch; N. Stefanou; C. Koenig (Vacancies and Interstitials in Metals and Alloys, 1987)
An expression for the interaction energy between two defects in a metallic compound within the framework of the frozen potential approximation is presented. The numerical application to vacancies in Al or TAl (T=Fe, Ni) shows that the electrostatic contribution of the screening charge around each defect can predominate over the one-particle term.